Hierarchical grid conversion. (October 2016) - Mahdavi-Amiri, Ali; Harrison, Erika; Samavati, Faramarz
Abstract: Hierarchical grids appear in various applications in computer graphics such as subdivision and multiresolution surfaces, and terrain models. Since the different grid types perform better at different tasks, it is desired to switch between regular grids to take advantages of these grids. Based on a 2D domain obtained from the connectivity information of a mesh, we can define simple conversions to switch between regular grids. In this paper, we introduce a general framework that can be used to convert a given grid to another and we discuss the properties of these refinements such as their transformations. This framework is hierarchical meaning that it provides conversions between meshes at different level of refinement. To describe the use of this framework, we define new regular and near-regular refinements with good properties such as small factors. We also describe how grid conversion enables us to use patch-based data structures for hexagonal cells and near-regular refinements. To do so, meshes are converted to a set of quadrilateral patches that can be stored in simple structures. Near-regular refinements are also supported by defining two sets of neighborhood vectors that connect a vertex to its neighbors and are useful to address connectivity queries. Highlights: Refinements and simple grid conversions are combined. Grid conversions are obtained by modifying the connectivity of vertices. Transformations imposed by grid conversions and refinements are computed. We employ Grid Conversion to define new regular and semiregular refinements. We also employ it for extending patch-based data structures. Graphical abstract: